3D printing of microbial communities: A new platform for understanding and engineering microbiomes. Issue 3 (13th December 2022) - Krishna Kumar, Ravinash; Foster, Kevin R.
Abstract: 3D printing has emerged as a powerful way to produce complex materials on‐demand. These printing technologies are now being applied in microbiology, with many recent examples where microbes and matrices are co‐printed to create bespoke living materials. Here, we propose a new paradigm for microbial printing. In addition to its importance for materials, we argue that printing can be used to understand and engineer microbiome communities, analogous to its use in human tissue engineering. Many microbes naturally live in diverse, spatially structured communities that are challenging to study and manipulate. 3D printing offers an exciting new solution to these challenges, as it can precisely arrange microbes in 3D space, allowing one to build custom microbial communities for a wide range of purposes in research, medicine, and industry. Abstract : Many microbes naturally live in diverse, spatially structured communities, that are challenging to study and manipulate. 3D printing offers an exciting new solution to these challenges, as it can precisely arrange microbes in 3D space, allowing one to build custom microbial communities for a wide range of purposes in research, medicine, and industry.